True Stories of the Strange & Unknown - Pinkney, John; Illustrated by Anne Spudvilas (Australia The Five Mile Press Ltd, 2008)
Contains true reports of weird and mysterious events, including haunted house horrors, UFOs that swoop on schools, people who see the future and uncanny animals. Suggested level: intermediate, secondary.
Including Pictures
Keywords: Parapsychology -- Supernatural -- Curiosities and wonders